Peran Pesantren dalam Era Digital - Oktaria, Auline; Khoirul, Khoirul; Fitriyenni, Srigustia; Paiman, Paiman; Irfan, Maulidul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This research aims to find out more deeply about the role of Islamic boarding schools in the digital era that emerged amid the Industry 4.0 and Society 5.0 markets. This research uses a type of qualitative research with a descriptive analysis method and describes it in a systematic, comprehensive, and holistic manner. Then the results of research on the role of Islamic boarding schools in the digital era can utilize various kinds of technology instead of being tossed around by the world of technology. Islamic boarding schools can also take advantage of digital technology in bureaucracy, administration, and in preaching. There are at least two constrictive steps that can be taken by Islamic boarding schools, namely Islamic boarding schools must be able to adapt to the times without losing their characteristics as Islamic boarding schools, and be able to fill digital space wisely. Islamic boarding schools are also undergoing reconstruction in facing the era of Society 5.0, especially in terms of curriculum, they must develop leadership competencies, language skills, IT literacy, writing skills, problem-solving, and critical thinking. As well as the efforts of Islamic boarding schools to enter into PISA, namely implementing HOTS Literacy-based learning, carrying out trials of questions in a format like the PISA test questions, increasing the competence of educators in Islamic boarding schools in HOTS Literacy-based learning, increasing the competence of educators in Islamic boarding schools in developing learning tools. which leads to PISA through Micro-Learning workshops, and provides links to simulation questions for PISA that are easily accessible to students.